Frequent Countermeasure Usage by Narcissistic Examinees in the Concealed Information Test - Elaad, Eitan; Zvi, Liza (Frontiers in Psychology, 2019)
Narcissistic dimensions and self-assessed lie and truth-telling and detecting abilities were used to predict deliberate attempts to influence the outcomes of the Concealed Information polygraph Test. In this study, which used a fabricated murder scenario, 241 participants were randomly assigned to four experimental conditions in a 2 × 2 factorial design. Two guilt conditions (guilty and innocent) were crossed with two countermeasures conditions (with or without countermeasure instructions). One group consisted of 120 informed guilty participants who were offered the opportunity to give a false response to neutral items by verbally answering “yes,” by which they falsely confirmed that the item is relevant to the murder case. Participants were told that frequent lying would confuse the polygraph and help them pass the test. Another informed guilty group (41 participants) was not given the opportunity to use countermeasures. Two control groups of 40 participants each were unaware of the critical items. One control group used countermeasures while the other did not. Narcissistic dimensions and self-assessed lie-telling ability correlated positively with frequent use of countermeasures. Conflicting results about the relation between countermeasure usage and physiological responses to critical items were obtained.